Atributos físico-químicos em argissolos tratados com vinhaça por 25 anos no Estado de Alagoas - Silva, Cícero Alexandre (2013)
The sugarcane is a raw material which after industrialization originates derivatives, like sugar and alcohol, extremely important for the country economical income. The process of fermentation of the broth and posterior distillation originate alcohol and vinasse. The last was earlier considered as a pollutant, however, nowadays it is carefully used for the improvement of biological, physical and chemical properties of the soil. The present work aims to evaluating, in laboratory, the modifications and displacements of some physical and chemical attributes in two clayish soils that had received vinasse for more than 25 years, in the factories Marituba (UMA) and Sto Antonio (USA), in the sugar cane region of Alagoas state, Brazil. The soil samples were collected in five layers (0-10, 10-20, 20-40, 40-70 and 70-100 cm) of depth, using the factorial [(2) plant (2) +vinasse (+v)/ -vinasse (-v) - (5) layers], 22x5 totalizing twenty treatments with four repetitions. From the results, it was noticed that vinasse promoted significant alterations in the soil, in accordance with the variance analysis (ANAVA), for with 0,01 of probability for test F, the attributes: pH, P, K+, Ca2++Mg2+, Total Organic Matter in Soil (OMS), Water Soluble Carbon (WSC), Potassium Saturation in the Cation Exchange Capacity (CEC) and porosity, The variables Soil Density (SD) and clay had presented significant differences, 0,05 level of probability and sands had been non-significant (NS). For the changeable layers in the profile of the ground, the parameters that had significance in 1% were; pH, P, K+, Ca2++Mg2+, OMS, WSC, CEC, sands and porosity, while the variable CEC and SD had been non-significant (NS). In the interaction of vinasse with layers the parameters that had significant differences for F test 0,01 were P, K+, Ca2++Mg2+, MOS, CTC, DS, % K+ CTC and sands, with significant difference of 0,05 for pH, CSA and clay. In the interaction of vinasse with layers, the differences 0,01 had been for P, Ca2++Mg2+, OMS, WCS, and % K+ CTC, of 0,05 of probability, the variables CTC and DS presented significant differences, already pH, K+, CEC, sands, clay and porosity had been NS. Comparing the averages among areas with and without vinasse, for the test of Tukey 0,05, have average higher for layers of the area that received vinasse: pH, P, K+, Ca2++Mg2+, WCS, SD and % K+ CTC. They had been similar for CEC and sands, however, in the area that did not receive vinasse, OMS, clay and porosity had presented higher values. The data obtained in this study indicate that the addition of vinasse was beneficial to the soil and therefore it is recommended to maintain its use, on the comparison between the benefit and the damage it can cause stillage.